Magnetic cross-linked enzyme aggregates (MCLEAs) applied to biomass conversion - Lucena, Guilherme Nunes [UNESP]; dos Santos, Caio Carvalho [UNESP]; Pinto, Gabriel Cardoso [UNESP]; da Rocha, Caroline Oliveira [UNESP]; Brandt, João Victor [UNESP]; de Paula, Ariela Veloso [UNESP]; Jafelicci Júnior, Miguel [UNESP]; Marques, Rodrigo Fernando Costa [UNESP] (Elsevier, 2019)
The increasing energy and sustainable materials demand requires the development of renewable production technologies to meet current global demands. Certainly, the progress for a sustainable development goes through the use of renewable and versatile raw materials, as the lignocellulosic biomass, in terms of application in energy, materials and environment sciences. The key role in the use of lignocellulosic biomass as renewable raw material has been its conversion to C6 and C5 sugars, which can be converted in different materials by several biological and chemical routes. Although its recalcitrance nature and high cost of the enzyme that promotes such conversions, obtaining a magnetic cross-linked enzyme aggregates (MCLEAs) has emerged as a green and sustainable technology to overcome these problems. This class of nanohybrids materials can significantly improve enzyme stability, activity and its recovery, decreasing cost of the process and adverse consequence of use of fossil raw materials. So, this review intends to shows the potential and recently advances of MCLEAs applied to biomass conversion to value-added chemicals, fuels and materials.
Keywords: Enzyme immobilization; Magnetic nanoparticles; Sustainable development